(untitled) (Innovative Applications of AI, 2024)
Guided by collaborative theory, this study establishes a data sharing platform with blockchain as the core. Taking the application scenario of digital identity as an example, the data sharing platform adopts an authorization-based consensus mechanism (PoA) combined with Practical Byzantine Fault Tolerance (PBFT) to explore the collaborative innovation application of the government affairs system. The collaborative innovation application has achieved inter-departmental paperless approval among multiple government departments, realizing "zero running" for citizens in handling affairs in more than 20 government affairs scenarios.